An efficient tabu search algorithm to the cell formation problem with alternative routings and machine reliability considerations - Chung, Shu-Hsing; Wu, Tai-Hsi; Chang, Chin-Chih (My University, 2011)
Cell formation is the first step in the design of cellular manufacturing systems. In this study, an efficient tabu search algorithm based on a similarity coefficient is proposed to solve the cell formation problem with alternative process routings and machine reliability considerations. In the proposed algorithm, good initial solutions are first generated and later on improved by a tabu search algorithm combining the mutation operator and an effective neighborhood solution searching mechanism. Computational experiences from test problems show that the proposed approach is extremely effective and efficient. When compared with the mathematical programming approach which took three hours to solve problems, the proposed algorithm is able to produce optimal solutions in less than 2 s. (C) 2010 Published by Elsevier Ltd.
Keywords: Cell formation; Alternative process routings; Machine reliability; Tabu search; Mutation operator